1999
DOI: 10.1099/13500872-145-2-495
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of the thiD/J gene of Escherichia coli encoding a thiamin-synthesizing bifunctional enzyme, hydroxymethylpyrimidine kinase/phosphomethylpyrimidine kinase

Abstract: A 1.7 kb DNA fragment isolated from an E. coif genomic library was able to complement the thiamin requirement of strains carrying the thiM, thil and thiD mutations. The three genes encode hydroxyethylthiazole kinase, hydroxymethylpyrimidine (HMP) kinase and phosphomethylpyrimidine (HMP-P) kinase, respectively. Sequence analysis revealed that the 1.7 kb fragment contained two ORFs of 708 bp and 801 bp. The former ORF complemented the thiM mutation and the latter ORF both the thil and thiD mutations. The latter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 24 publications
0
32
0
2
Order By: Relevance
“…ThiJ was a thiamin biosynthesis enzyme that catalyzed the phosphorylation of hydroxymethylpyrimidine (HMP) to HMP monophosphate. The enzyme was primarily studied in E. coli (Mizote et al, 1999), but has not been characterized in plants. There are two other Arabidopsis proteins that are highly homologous to the cabbage protein (BLASTP value E < 10 −70…”
Section: Resultsmentioning
confidence: 99%
“…ThiJ was a thiamin biosynthesis enzyme that catalyzed the phosphorylation of hydroxymethylpyrimidine (HMP) to HMP monophosphate. The enzyme was primarily studied in E. coli (Mizote et al, 1999), but has not been characterized in plants. There are two other Arabidopsis proteins that are highly homologous to the cabbage protein (BLASTP value E < 10 −70…”
Section: Resultsmentioning
confidence: 99%
“…However, in vitro studies have shown that HMP itself does not bind to the riboswitch (27), and our own studies here indicate that neither HMP nor HMP-P competes with HMP-PP binding. If we therefore assume that this also applies in vivo, then it is highly plausible that HMP is pyrophosphorylated by THID (32) and can bind to the riboswitch in a similar manner to TPP. Direct evidence that HMP-PP binds to the THIC riboswitch is provided by equilibrium dialysis (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This family includes proteins involved in RNA-protein interaction regulation, thiamine biosynthesis, and protease activity, which do not appear to be related to one another. The role of this family remains unclear, and most of the members are predicted proteins that have, to our knowledge, not been functionally analyzed except for ThiJ, which catalyzes hydroxymethylpyrimidine phosphorylation in the thiamine biosynthetic pathway (35,36), and for intracellular proteases (PfpI and PH1704) in hyperthermophilic archaea (30,31). Here, we discovered that the members of the ThiJ/PfpI family and isonitrile hydratase (which is an enzyme playing a novel physiological role in isonitrile degradation) comprise a novel superfamily.…”
Section: Fig 4 CD Spectra Of the Wild-type And Mutant Isonitrile Hymentioning
confidence: 99%